Modeling of Doped Amplifiers and Filters in Hybrid Optical Communication Systems - Ozdemir, M. Emin; Unverdi, N. Ozlem (IEEE, 2024)
The effects of doped optical amplifiers and optical filters used in hybrid fiber optic and Free Space Optics (FSO) communications on data transmission performance were studied. The performances of doped optical amplifiers EDFA (Erbium Doped Fiber Amplifier), YDFA (Ytterbium Doped Fiber Amplifier), PDFA (Praseodymium Doped Fiber Amplifier) and HDFA (Holmium Doped Fiber Amplifier) were evaluated in the reference communication system designed in OptiSystem 20.0 simulation software. With the same setup, the performances of Bessel, Gaussian, Butterworth, and Chebyshev optical filters were evaluated by comparing their quality factors, eye diagrams, and BER (Bit Error Rate).
Keywords: Communication technologies; fiber optic communication; free-space optical communication; optical amplifier; optical filter; Computer Science; Engineering; Telecommunications